Acúmulo de carboidratos no desenvolvimento de tomateiro tratado com produtos químicos - Pereira Ramos, Anamaria Ribeiro [UNESP]; Esteves Amaro, Amanda Cristina [UNESP]; Macedo, Ana Claudia [UNESP]; Souza, Essione Ribeiro [UNESP]; Rodrigues, Joao Domingos [UNESP]; Ono, Elizabeth Orika [UNESP] (Univ Estadual Londrina, 2015)
This work had the purpose to study the physiological effects of pyraclostrobin, boscalid, plant growth regulators and plant extract on the accumulation of carbohydrates during the development of tomato plants (Solanum lycopersicum L.), hybrid Giuliana, in protected environment conditions. The treatments were: T1- control; T2- pyraclostrobin 0.2 g L-1; T3- boscalid 0.075 g L-1, T4- pyraclostrobin 0.2 g L-1 + boscalid 0.075 g L-1, T5- IBA + GA(3) + kinetin 375 mg L-1, T6- GA(4+7) + benzylaminopurine 100 mg L-1 and T7- plant extract 100 mg L-1. The carbohydrate accumulation curve was accomplished with 5 samples, at 20-day intervals between evaluations, the 1st evaluation being carried out at 30 days after transplantation, on the day of the first treatment application. At each sampling the plants were separated in stem, leaves and fruits, of which the contents of total soluble sugars, reducing sugars and saccharose were evaluated. The effects of the treatments on chlorophyll content and gas exchanges were also evaluated. The experimental design was completely randomized, with 4 repetitions and 6 destructive evaluations during the development, with 1 plant per experimental unit for each sampling. The pyraclostrobin and boscalid applied in isolation and/or combined favor the increase of carbohydrates in leaves, stems and fruits of tomato hybrid Giuliana.

Este trabalho teve como objetivo estudar os efeitos fisiológicos da piraclostrobina, boscalida, reguladores vegetais e extrato vegetal no acúmulo de carboidratos durante o desenvolvimento de plantas de tomateiro (Solanum lycopersicum L.), híbrido Giuliana, em condições de ambiente protegido. Os tratamentos estudados foram: T1- testemunha; T2- piraclostrobina 0,2 g L-1; T3- boscalida 0,075 g L-1, T4- piraclostrobina 0,2 g L-1 + boscalida 0,075 g L-1, T5- IBA + GA3 + cinetina 375 mg L-1, T6- GA4+7 + benzilaminopurina 100 mg L-1 e T7- extrato vegetal 100 mg L-1. A curva de acúmulo de carboidratos foi realizada com cinco amostras, em intervalos de 20 dias entre as avaliações, sendo a 1ª avaliação realizada aos 30 dias após o transplantio, no dia da primeira aplicação dos tratamentos. A cada coleta as plantas foram separadas em caule, folha e frutos, nos quais foram avaliados os teores de açúcares solúveis totais, açúcares redutores e sacarose. Também foram avaliados os efeitos dos tratamentos no teor de clorofila e nas trocas gasosas. O delineamento experimental adotado foi inteiramente casualizado, com quatro repetições e seis avaliações destrutivas ao longo do desenvolvimento, sendo uma planta por unidade experimental em cada amostragem. A piraclostrobina e a boscalida aplicados isolados e/ou combinados favoreceram o incremento de carboidratos nas folhas, caules e frutos de tomate ‘Giuliana’.
Accumulation of carbohydrates in the development of tomato plants treated with different chemical products
Keywords: Solanum lycopersicum L.; Strobilurin; Pyraclostrobin; Boscalid; Gas exchange; Solanum lycopersicum L.; Estrobirulina; Piraclostrobina; Boscalida; Trocas gasosas